Beneath - Sullivan, Ariel (Ballantine Books, an imprint of Random House, 2026)
"Hundreds of years before the Illum ruled supreme, humanity risked everything to rebuild after a devastating war in this explosive dystopian romance and prequel to Conform. Twenty-three-year-old Sasha Cadell knows time is running out in the underground city, filled with survivors of the nuclear fallout six years ago. She works in the Expansion Sector, trying to escape the memories of those she lost. Her bleak existence is upended when Tristian Hayes, a stunningly handsome, frustratingly determined commander of the Force, recruits her to join him and his elite team of soldiers as they embark on a secret mission to the surface. Sasha is thrust into brutal training with stakes far beyond mere survival. The fate of the remaining humankind depends on their success--or failure. As she confronts her own demons, Sasha finds both allies and foes in the training program, as well as a sizzling attraction between her and Tristian that threatens the walls she's built around her heart. But under the surface, secrets and deception run as rampant as illnesses. And not everyone will survive the rise of a power more terrifying than anything they've ever known."--Bookcover.